A Framework for Playable Social Dialogue - Treanor, Mike; McCoy, Josh; Sullivan, Anne (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2016)
Non-player characters in games generally lack believability and deep interactivity. The AI system Ensemble begins to tackle this by modeling social state and behaviors for game characters. With previous versions of Ensemble, the player initiates social exchanges and the system generates the dialogue and outcome and displays them in their entirety. In this paper we present an extension to Ensemble comprised of a model of playable social dialogue called social practices. Social practices increase the playability of character interactions and add interactivity at each stage of dialogue. Additionally, this work enables a more modular form of authoring to support the additional complexity.